LEGAL AUDIT OLEH INTERNAL CONTROL PADA PERUSAHAAN PEMBIAYAAN PT. MAYBANK INDONESIA FINANCE CABANG SAMARINDA - Fahriansyah Ramli (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACT. Research with the title of writing the law above, was carried out with the aim to examine the implementation of the Legal Audit conducted by PT. Maybank Indonesia Finance Branch Samarinda in reviewing the feasibility of prospective borrowers to receive financing facilities seen from the validity of credit terms documents provided by prospective borrowers to the financing company. In addition, to find out the implementation of the Legal Audit on the handling of debtors who have experienced bad credit at PT. Maybank Indonesia Finance Samarinda branch.Based on the results of the research that the author did that the legal audit is first done by checking the marketing documents, then checking the dealer documents and then proceed with the examination of the binding documents. Implementation of Legal Audit at PT. The Maybank Indonesia Finance branch of Samarinda is done by comparing these documents with the Standard Operating Procedure (SOP) which is made based on the laws and regulations, then if there are still doubts and irregularities, then an inspection is carried out in the field. Keywords : legal audit.